How Does Social and Work Life Change for Fathers of Children With Cancer?. (October 2022) - Yi, Jaehee; Kim, Min Ah; Sang, Jina; Gonzalez-Pons, Kwynn M.
Caring for a child with cancer greatly affects fathers' social lives, with fathers experiencing conflicts between work demands and their desire to be with their sick child. To date, fathers' unique experiences of caring for a child with cancer remain poorly understood. This study aimed to understand the impact of a child's cancer diagnosis on the social and work relationships of their father through in-depth interviews with 20 Korean fathers of a child with cancer within 5 years of the diagnosis. Thematic analysis yielded five themes related to how a child's cancer diagnosis affected the father's relationships at work and in social situations: (a) shifting priorities, (b) changes in work, (c) support and struggles at work, (d) not being social out of guilt, and (e) pent-up stress. Overall, the findings highlight that fathers experienced conflicting roles and constraints in social relationships after their child's cancer diagnosis. This should be considered when developing and implementing social services for families with children diagnosed with cancer.